Fantastic 4. Rise of the Silver Surfer [videorecording (DVD)] - Story, Tim; Gruffudd, Ioan; Alba, Jessica, 1981-; Evans, Chris, 1981- (20th Century Fox Home Entertainment, 2007)
When the Silver Surfer arrives on Earth, army General Hager demands that Reed Richards create a sensor to track him and find out what he's doing on Earth. The only problem is that Richards is helping Sue Storm plan their rescheduled wedding. Ben Grimm is heating up his relationship with Alicia and Johnny Storm is trying to get sponsorships and girls. Returning is Victor Von Doom, who gladly offers to assist the military in figuring out what the Silver Surfer is all about.